2018
DOI: 10.1021/acssuschemeng.7b04508
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Pickering Emulsion Stabilized by Silica Nanoparticles Dispersed with High-Molecular-Weight Amphiphilic Alginate Derivatives

Abstract: O/W Pickering emulsions formed with silica nanoparticles adsorbed with amphiphilic alginate derivatives produced a longer stability. Ugi-Alg was obtained by a mild and efficient Ugi four-component condensation reaction, and its structure of Ugi-Alg was confirmed by 1 H nuclear magnetic resonance and Fourier transform infrared spectroscopies. Dynamic light scattering and transmission electron microscopy measurements were then performed to characterize the aggregation behavior of SiO 2 /Ugi-Alg mixture in aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…[46] Based on Stokes' equation, [47] it is well-known that creaming is accelerated by high droplet size and low viscosity of the continuousp hase. [48] The enhanced viscosity at pH 3s lowed the dropletm igration rate (Video V3) and the number of collisions between oil droplets (Figure 3). Therefore, lower viscosity along with as maller droplet size improved the emulsion stability at pH 3.…”
Section: Rheological Characteristicsmentioning
confidence: 94%
“…[46] Based on Stokes' equation, [47] it is well-known that creaming is accelerated by high droplet size and low viscosity of the continuousp hase. [48] The enhanced viscosity at pH 3s lowed the dropletm igration rate (Video V3) and the number of collisions between oil droplets (Figure 3). Therefore, lower viscosity along with as maller droplet size improved the emulsion stability at pH 3.…”
Section: Rheological Characteristicsmentioning
confidence: 94%
“…Acid-catalyzed dehydration of C5 sugars, such as xylose and arabinose gives furfural, a very important chemical for the production of fuel additives and polyester monomers. [83][84][85] Cui et al 83 indicated that the co-operative interaction of Hb zeolite with g-butyrolactone-water solvent system enables both selective C-C bond cleavage of acyclic hexoses into pentoses and the subsequent dehydration into furfural. The obtained furfural yields from fructose, glucose, and cellulose were 63.5, 56.5, and 38.5%, respectively.…”
Section: Pristine and Substituted Zeolitesmentioning
confidence: 99%
“…Pickering emulsions make it possible to tune the emulsion properties in terms of droplet diameter and proper surface functionalization of the NPs to achieve high activity and a prolonged shelf life of the incorporated microorganisms. Silica NPs is an eco-friendly 32 emulsion stabilizer, which enables the introduction of additional functionalities to the product, such as UV protection and humidity control. This can be done by chemical modification of the silica NPs with organosilanes.…”
Section: Introductionmentioning
confidence: 99%